CATCHING THE SLIPPERY FISH: WILL LIFESTYLE AUDITS NET THE CORRUPT IN UGANDA - Tiberindwa, Zakaria (Journal of Anti-Corruption Law, 2024)
Uganda is one of the African countries that have embraced lifestyle audits as a tool against corruption in the public service. In November 2021, the Inspector General of Government announced that the Inspectorate of Government would subject public officials to lifestyle audits as a means to fight corruption in government. There is evidence that when lifestyle audits are effectively implemented, they can be a viable anti-graft mechanism. Yet, resource limitations as well as other legal and policy constraints may complicate the implementation of lifestyle audits. Moreover, their constitutional legitimacy may be contested due to the intrusion on the privacy rights of individuals who are subjected to such audits. Also, the shifting of the burden of proof to those implicated to explain any disparities in their wealth and sources of income may infer a negation of the presumption of innocence. Furthermore, there have also been suggestions that they may encourage arbitrary deprivations of property. In Uganda, there has been scanty academic discourse on the likely legal and policy challenges that may constrain the effective implementation of lifestyle audits to counter corruption. This paper therefore seeks to discuss some of the legal and policy limitations that may constrain the implementation of lifestyle audits in Uganda and make suggestions on how some of the limitations can be overcome in the circumstances. The paper reviews various laws, policies and jurisprudence regarding lifestyle audits, as well as books and articles on the subject.